Perancangan Model Simulasi Tata Letak Gudang Bahan Baku untuk Meminimasi Waktu Pengambilan Bahan Baku Pada PT. Springville Indonesia dengan Menggunakan Metode Dedicated Storage - Michael Yonatan Kristanto; Sucipto Adisuwiryo; Parwadi Moengin (JURNAL TEKNIK INDUSTRI, 2018)
PT. Springville Indonesia is a company engaged in the mattress industry. The product produced is a mattress with two types,namely the type of bed and latex. The main raw material is foam. Problems found in the raw material warehouse of PT. SpringvilleIndonesia is a system of laying out raw materials that are less organized so that it causes operators difficulty in taking raw materialswhich causes the time to take raw materials to experience delays in the process of sending raw materials to the production floor. Thisproblem is caused by the layout of the raw material warehouse which is not good and the raw material has not been neatly arrangedand there is no alley (the path used for the process of receiving and retrieving raw materials). The purpose of this study is to design asimulation model of improvement in raw material warehouse layout to minimize the time taken for raw materials.Evaluate the initial layout of the raw material warehouse using a checksheet. From the checksheet, it was continued by designing theinitial raw material warehouse layout. then designed the initial raw material warehouse layout simulation model. After the initialwarehouse layout of raw materials was declared valid, repairs were made to the raw material warehouse layout problems by changingthe warehouse layout of the raw materials so that there was an alley for the raw material collection and receiving path. Using thededicated storage method as a proposal for the raw material warehouse layout which is then verified and validated. The raw materialin the form of foam must be placed in the front so that the operator is easy to pay attention to the condition of the foam. This causesfoam raw materials not to be included in the calculation of dedicated storage.